THE ESTIMATION OF ADAPTABILITY OF WINTER BARLEY VARIETIES IN THE SOUTH OF RUSSIA - E. G. Filippov; A. A. Dontsova; R. N. Bragin (Зерновое хозяйство России)
The improvement of yield stability largely depends on responsiveness to favorable growing conditions and resistance to stress factors. The promising varieties should have stable yields, resistance to unfavorable environmental conditions, such as winter resistance and drought tolerance. In this regard, a purposeful breeding for adaptability, i.e. resistance to stress factors is of great importance. The purpose of the research was to study the adaptability and stability of winter barley varieties. The estimation was carried out on the experimental field of the FSBSI ARC “Donskoy”, which is located in the southern zone of the Rostov region. Through three years, 28 winter barley varieties of domestic and foreign breeding were studied. The location of the plots is systematic in double sequence; the area is 10 m². The calculation of ecological plasticity was carried out according to the method of S. A. Eberchart, W. A. Rassel (1966) (ed. by V. A. Zykin (2005)) using the statistical data processing program Statistica 10. It has been established that the most responsive varieties (bi > 1) to the improvement of growing conditions were ‘Erema’ (bi = 1.60), ‘Foks 1’ (bi = 1.64), ‘Skala’ (bi = 1.61), ‘Explorer 8’ (bi = 1.81) and ‘Capten’ (bi = 2.02). These varieties due to a high level of agricultural technology provide maximum yields. At an extensive background it is better to use the varieties ‘KWS-2-117’ (bi = 0.28), ‘KWS – 2–234’ (bi = 0.48). The most stable varieties of the studied foreign ones were the varieties ‘Wintwalt’ and ‘Explorer 4’ (σ²d = 0.04). Through the years of study, the variety ‘Marusya’ (RF) had the highest yield with a linear regression coefficient bi = 0.54, which indicates great stability of this variety.